Vinyl Composite Tile Surrogate for Mechanical Slip Testing. Issue 2 (3rd April 2019) - Chanda, Arnab; Reuter, Aiden; Beschorner, Kurt E.
OCCUPATIONAL APPLICATIONS: This study aimed to identify a durable laboratory-grade surrogate material for vinyl composite tile (VCT) suitable for footwear traction testing. To conduct this investigation, eight polymer tiles (cast nylon, polyethylene, polycarbonate, acetal, Delrin, PTFE, polypropylene, and nylon) were tested across different shoes and contaminants (water, sodium laurel sulfate, and oil), and the available coefficient of friction (ACOF) was measured and compared with that of two designs of VCT. Shoe ACOF performance on cast nylon tile with oil contamination was generally applicable to both VCTs in oil contaminated condition. Shoe ACOF performance for none of the eight candidate tiles were applicable to the VCTs for other contaminated conditions. Cast nylon is anticipated to serve as a durable VCT surrogate, for standard slip testing of footwear in oil-contaminated conditions. TECHNICAL ABSTRACT Background: Vinyl composite tile (VCT), which is a common flooring in workplaces, is sometimes utilized as the standard floor material for mechanical slip testing experiments. Unfortunately, VCT is a sub-optimal standard test material, since it changes over time and is difficult to manufacture consistently.Purpose: This study aimed to identify a durable laboratory-grade substitute flooring that could provide traction results that are representative of footwear performance on VCT.Methods: Eight polymer tiles (cast nylon, polyethylene, polycarbonate, acetal, Delrin, PTFE, polypropylene, and nylon) were tested and the available coefficient of friction (ACOF) was measured and compared with that of two VCT designs. First, a screening test was performed to identify good material candidates based on six shoes and two contaminants (water and oil). Two surrogate candidate tiles were then tested across 17 shoes and 3 contaminant conditions (water, sodium laurel sulfate, and oil).Results : Cast nylon tile was found to be the most generalizable VCT surrogate, exhibiting strong correlations with both VCTs for oil contamination. None of candidates were representative of the VCTs for other contaminants. Conclusions: Cast nylon may be a useful alternative for VCT for standard slip testing of footwear in oily conditions.